2019
DOI: 10.1248/cpb.c19-00103
|View full text |Cite
|
Sign up to set email alerts
|

Study on Redox Properties and Cytotoxicity of Anthraquinone Derivatives to Understand Antitumor Active Anthracycline Substances

Abstract: This study demonstrates the relation between the redox properties and cytotoxicity of anthraquinone derivatives with a hydroxyl and methoxy group. The redox behavior of the anthraquinone derivatives was initially observed via cyclic voltammetry and their characteristics were investigated using molecular orbital calculations. The cytotoxicity of the anthraquinone derivatives was then evaluated using human leukemia HL-60 and H 2 O 2 resistant HP100 cells, and its correlation with the redox properties of these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Cytotoxic studies against HL-60 and HP100 cells (using LDH activity assay) indicated that oxidized radicals played a significant role in inducing cell death. 78 The toxicity towards HL-60 increased with the increase in the concentration of 56. However, the toxicity in relation to HP100 was less than half the toxicity to HL-60, indicating that H 2 O 2 is involved in the process leading to cell death.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 98%
See 1 more Smart Citation
“…Cytotoxic studies against HL-60 and HP100 cells (using LDH activity assay) indicated that oxidized radicals played a significant role in inducing cell death. 78 The toxicity towards HL-60 increased with the increase in the concentration of 56. However, the toxicity in relation to HP100 was less than half the toxicity to HL-60, indicating that H 2 O 2 is involved in the process leading to cell death.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 98%
“…Specifically, the cytotoxicity observed against HL-60 could be ascribed to reactive oxygen species (ROS) originating from electron transfer to oxygen accompanying the formation of reduced or oxidized compound 56 radicals. 78 In another investigation, Roa-Linares et al synthesized 27 terphenyl-1,4-naphthoquinone (NQ), 1,4-anthraquinone (AQ), and heterocycle-fused quinone (HetQ) derivatives to evaluate their cytotoxicity against HeLa and Jurkat tumour cell lines. Compound 57 was found to be the most active against the tested cell lines, and the IC 50 values of 57 observed to be cell lines 0.010 μM, 1.4 μM, and 231.9 μM against HeLa ATCC CRL-1958, Jurkat ATCC TIB-152, and Vero ATCC CCL-81, respectively.…”
Section: Development Of Non-specific Cytotoxic Anthraquinone Derivativesmentioning
confidence: 99%
“…The 9,10-anthracenedione scaffold is likely to interfere with the parasite redox system as anthraquinones can mediate the production of hydrogen peroxide or ROS via oxygen reduction in situ ( Campos-Martin et al., 2006 ). This is a feasible antichagasic mechanism as anthraquinones have been shown to interfere with redox reactions in cells ( Okumura et al, 2019 ). ROS generation is also the postulated mode of action of the approved antichagasic drug benznidazole ( Pedrosa et al, 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Besides their application as pigments or dyes in textile, photographic, cosmetic and other industries (Wang et al, 2011), anthraquinone derivatives have been used for centuries for medical applications, for example, as laxatives (Oshio et al, 1985), antioxidants (Yen et al, 2000), antimicrobial (Xiang et al, 2008;Yadav et al, 2010) and anitiviral (Alves et al, 2004) agents. Their redox properties and cytotoxicity have been investigated recently (Okumura et al, 2019). Anthraquinone derivatives exhibit various applications in supramolecular and electro-analytical chemistry (Czupryniak et al, 2012).…”
Section: Chemical Contextmentioning
confidence: 99%